Multiple forest use through commercial sport hunting: lessons from a community-based model from the Petén, Guatemala - Baur, E.H.; McNab, R.B.; Williams, L.E.; Ramos, V.H.; Radachowsky, J.; Guariguata, Manuel R. (2011)
The “Proyecto Pavo” is a project dedicated to the conservation of the Ocellated Turkey (Meleagris ocellata) through sustainable use of the species in multiple-use, community-managed forest concessions of the Maya Biosphere Reserve in Petén, Guatemala. Since 2000, the project has conducted selective turkey harvests, performed related research, and promoted the conservation benefits of managed sport hunting for this species. Field activities of the project feature providing high-quality Ocellated Turkey hunts to sport hunter clients. Participating concessions benefit directly from harvest revenues of a resource that was not previously exploited commercially and indirectly from affiliated project activities. The project began operations in a single concession on an experimental basis and evolved into a commercial enterprise operating in multiple concession units. The project has overcome numerous development and operational challenges, including compatibility issues with timber and NTFP extraction. Under proper circumstances, carefully designed sport hunting programs can offer profitable and sustainable forest product diversification alternatives that are highly compatible with tropical multiple-use management and forest conservation objectives.